Curly birch (Betula pendula var. carelica), wooden ´marble´ from Finland − soon easily available - Viherä-Aarnio, Anneli; Hagqvist, Risto (Natural Resources Institute Finland, Luke, 2017)
Curly birch (Betula pendula var. carelica (Mercklin) Hämet-Ahti) is a special variety of silver birch, known for its hereditary and unique, highly decorative curly-grained and brown-figured wood. It is the most highly-priced variant of native tree species in the Nordic countries. Curly birch logs and veneer are used for furnishing and paneling e.g. banks, offices, luxury homes, ships and expensive cars. Wood with smaller dimensions is used in carpentry for highly valued products such as gifts, souvenirs, tools and furniture. Curly birch occurs naturally, but rare, in Northern Europe and parts of Eastern and Central Europe. Its cultivation has a long tradition in Finland. Interest in commercial cultivation of curly birch has, however, increased significantly since the 1980’s. As a result some 6500 hectares of curly birch stands have been established. They will soon start reaching their rotation age (35-50 years). Small-sized wood from thinnings is already available in abundance. The significantly increasing availability of this exceptionally beautiful wood resource makes it possible to develop new wood products based on this, now cultivated, variant. The wood material is suitable also for premium products with high class design. Earlier the poor availability of curly birch wood has prohibited developing such products. Now wood will soon be available regularly in larger quantities than today, enough for both domestic use and export. Silvicultural management of curly birch has to be done with special care, from plantation establishment, through right-timed thinnings to branch pruning and final cutting. In this article the wood characteristics and utilization, silvicultural practices and the rapidly changing market issues of this wooden ´marble´ are reviewed.
Keywords: curly birch; Betula pendula; Betula; wood properties